Public transport investments, commuting and gentrification: Evidence from Copenhagen - Ismir Mulalic; Jan Rouwendal (Tinbergen Institute, 2022)
This paper considers the impact of the introduction of a metro network in the Copenhagen metropolitan area. Using travel surveys from years before and after the opening of the metro network, we observe a significant change in travel times, speeds and mode choice for commutes that can completely or partly be realized by the metro. Interest in the metro among the higher educated is much stronger than among the lower educated. House prices in the vicinity of the metro stations increased significantly. The total additional value of real estate generated by the metro is appr. 40% of the actual construction cost. The government captured a substantial part of the value generated by the metro by concentrating housing construction in some hitherto undeveloped areas close to metro stations. We use a gravity model to explore the implications of the metro for urban structure in an urban equilibrium context and find that all adjustment takes place in the housing market. The lower and medium educated face adjustments in housing attractiveness that counteract the initial impact of the metro. We find no evidence for such adverse effects on the higher educated, which suggest a close connection between the impact of the metro and gentrification in the Copenhagen.
Keywords: D1; R4; R1; 330; underground transportation; urban structure; public transport investment; commuting; gentrification